A Reality of secondary students with special needs in mathematics - Chavarría Arroyo, Gilberto (2013)
The purpose of this research was to gain knowledge about expectations, feelings, and perspectives of students with special needs in mathematics, in a high school context, to create a profile of these students. The focus of this research was placed on six students from eleventh grade that have this condition. The institution selected was a public academic high school, in the state of Heredia. The method used to collect and to analyze data was a case study. The main techniques included: class observation, a questionnaire, unstructured interviews to the teacher and to students, and clinical interviews for students with special needs. Among the relevant findings is it was evidenced an absence of modifications to the curriculum implemented by the teacher in mathematics classes, except for an extra lesson given to these students during written tests. Among the limitations of the focus students to learn mathematics, they used poor mathematics concepts and previous related knowledge. Another finding regards to the lack of communication among all the actors related to the process of implementing Curriculum modifications for students with special needs. Nevertheless, students with this condition help each other and in that way show their solidarity. Based on the findings, it is recommended that mathematics teachers must revisit concepts from previous contents studied, when participant students have concept knowledge limitations. Also, they ought to evaluate closely any advancement that students with special needs make.